Analysis of Students Environmental Attitudes as a Contribution to the Sustainable Development Goals (SDGs) - Al Idrus, Syarifah Wahidah; Rahmawati, Rahmawati; Kadir, Abdul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Environmental attitudes among university students play a crucial role in supporting the achievement of the Sustainable Development Goals through the development of responsible and sustainable behaviors. This study aims to analyze university students’ environmental care attitudes in the context of the Sustainable Development Goals (SDGs). A descriptive quantitative approach was employed, involving 121 students from the Chemistry Education Program, Faculty of Teacher Training and Education, Universitas Mataram. Data were collected using a 5-point Likert scale questionnaire covering three primary dimensions of environmental attitude-cognitive, affective, and conative-along with a commitment dimension toward the SDGs. The results indicate that all dimensions fall within high to very high categories, with the highest averages observed in the cognitive (4.32), affective (4,18) and SDGs commitment (4.25) dimensions. The conative dimension scored slightly lower (3.89), suggesting the existence of an attitude–behaviour gap between awareness and actual practice. Students demonstrate strong environmental knowledge and moral commitment, but have not fully translated these into consistent, sustainable behaviors. These findings underscore the need for more contextually relevant and action-oriented learning strategies based on the SDGs, such as project-based learning and eco-campus programs, to translate environmental awareness into tangible actions. Overall, the study emphasizes the strategic role of higher education in cultivating knowledgeable, committed, and sustainable-minded youth aligned with SDG 12, SDG 13, and SDG 15.